32.4: A Scalable, Collaborative, Interactive Light‐field Display System. Issue 1 (1st July 2013) - Klug, Michael; Burnett, Thomas; Fancello, Angelo; Heath, Anthony; Gardner, Keith; O'Connell, Sean; Newswanger, Craig
Abstract Light‐field displays provide a visual sense of presence by producing a full‐parallax three‐dimensional aerial and virtual image of portrayed subject matter that satisfies multiple depth cues and that can be engaged naturally and intuitively. This paper documents a comprehensive light‐field display system, including computation, photonics, and interaction system components, that is flexible and scalable, establishing a basis for application to both large‐scale collaborative and portable, mobile product architectures.